TECHNOLOGY OF ORGANIZING SOCIAL INITIATIVE IN FUTURE TEACHERS - Nishonova Kamola Shokirjon qizi (Western European Studies, 2025)
This article discusses the relevance of developing social initiative in the formation of the personality of future teachers, the scientific and theoretical foundations of pedagogical approaches and technological processes in this regard. At the same time, the content of the concept of social initiative, its importance in the educational process, and methods of its effective organization through modern design technologies are analyzed.
Keywords: Future teacher; social initiative; pedagogical technology